The Thick Red Line: Implications of the 2013 Chemical-Weapons Crisis for Deterrence and Transatlantic Relations. Issue 6 (2nd November 2017) - Lewis, Jeffrey; Tertrais, Bruno
Abstract : Whether or not American policy after the 2013 Syrian chemical-weapons attack was wise, its execution was bungled, causing unnecessary harm to the US– France relationship.